PENDAMPINGAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA UNTUK PENGELOLAAN BUMDESA ADAT CEPAKA KECAMATAN KEDIRI KABUPATEN TABANAN - I Ketut Yudana Adi; Ida Ketut Kusumawijaya; Kukuh Rian Setiawan (Synergy and Society Service, 2022)
Cepaka Village has a lot of potential that can be developed and managed by BUMDes. This business unit managed by BUMDes requires good management and accountability in its financial reporting. One form of accountability is to prepare financial reports. This community service program or PKM is carried out to assist in financial reporting of BUMDes business unit activities. The form of PKM carried out is in the form of assistance related to the preparation of financial reports. This activity was attended by all BUMDes managers. The results of the evaluation carried out after implementing the PKM show the understanding and ability to manage and report the finances of the Cepaka Indigenous BUMDes business unit.